2021
DOI: 10.3390/biomedicines9091104
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Decorated with Polar Groups and Blue Emitting BODIPY Dye: Synthesis, Cytotoxicity, Cell-Cycle Analysis and Anti-HIV Profiling

Abstract: Betulinic acid (BA) is a potent triterpene, which has shown promising potential in cancer and HIV-1 treatment. Here, we report a synthesis and biological evaluation of 17 new compounds, including BODIPY labelled analogues derived from BA. The analogues terminated by amino moiety showed increased cytotoxicity (e.g., BA had on CCRF-CEM IC50 > 50 μM, amine 3 IC50 0.21 and amine 14 IC50 0.29). The cell-cycle arrest was evaluated and did not show general features for all the tested compounds. A fluorescence micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
(61 reference statements)
1
7
0
2
Order By: Relevance
“…This paper described the synthesis of betulinic acid derivatives, their cytotoxicity, cell-cycle analysis, and anti-HIV profiling. The results of this study suggest that betulinic acid has a similar mechanism of inhibition as described in bevirimat [4].…”
supporting
confidence: 68%
“…This paper described the synthesis of betulinic acid derivatives, their cytotoxicity, cell-cycle analysis, and anti-HIV profiling. The results of this study suggest that betulinic acid has a similar mechanism of inhibition as described in bevirimat [4].…”
supporting
confidence: 68%
“…Therefore, in addition to lipophilicity, there are likely other factors that influence the bioactivity or cytotoxicity of these compounds. For example, MAPKs regulate mitochondrial metabolism [26], and some compounds were reported to target mitochondria for their cytotoxic or anti-inflammatory effects [24,27,28]. Thus, whether the triterpenoids reported in this study target mitochondria deserves to be addressed.…”
Section: Discussionmentioning
confidence: 97%
“…The anticancer effect was compared with BA and bevirimate, a BA-derivative with potent anti-HIV activity, which was abandoned in phase two clinical trials due to resistance acquisition. A SAR evaluation was performed on those derivatives that exhibited IC 50 values within the micromolar range ( Table 3 ) and revealed that BA-pyperazinyl derivatives induce slightly higher cytotoxic effects compared with BA-aminopropyl derivatives; in addition, the esterification of C3 with succinic acid or BODIPY-COOH diminished the overall cytotoxicity, thus suggesting that free C3 (BA 27) plays a key role in the occurrence of cytotoxic activity [ 65 ]. Although the study showed clearly superior cytotoxicity compared with BA and beviramat, the same effect was also exerted against normal cells, thus limiting their development as therapeutic compounds.…”
Section: Betulinic Acidmentioning
confidence: 99%